2017
DOI: 10.1136/bjophthalmol-2016-309837
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive method of monitoring retinal vasculitis in patients with birdshot chorioretinopathy using optical coherence tomography

Abstract: Evaluating large-vessel perivascular thickness on OCT scans may be a useful method for non-invasively monitoring posterior pole large-vessel retinal vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Interestingly, although none of the OCTA data showed an association with peripheral capillary leakage on FA, there was a correlation between peripheral capillary leakage on FA and perivascular-peripapillary and macular thickening on en-face wide-field thickness maps. In keeping, a previous study on patients with Birdshot chorioretinopathy has shown that perivascular thickening on thickness maps corresponds to vasculitis and may be used to follow phlebitis and disease activity in patients with respective disease 17. Our findings broaden the spectrum of evaluable diseases, which makes en-face thickness maps a promising, additional tool to follow patients with uveitis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, although none of the OCTA data showed an association with peripheral capillary leakage on FA, there was a correlation between peripheral capillary leakage on FA and perivascular-peripapillary and macular thickening on en-face wide-field thickness maps. In keeping, a previous study on patients with Birdshot chorioretinopathy has shown that perivascular thickening on thickness maps corresponds to vasculitis and may be used to follow phlebitis and disease activity in patients with respective disease 17. Our findings broaden the spectrum of evaluable diseases, which makes en-face thickness maps a promising, additional tool to follow patients with uveitis.…”
Section: Discussionsupporting
confidence: 78%
“…The degree of retinal thickness was graded according to the colour-coded thickness maps. Cool colours (green and blue) represent decreased thickness, while warm colours (yellow, orange and red) represent increased thickness 17. Qualitative analysis of capillary network abnormalities was then compared with FA.…”
Section: Methodsmentioning
confidence: 99%
“…Exudative vasculitis is usually evaluated by fundus fluorescein angiography (FFA) because it allows visualization of dye leakage through the impaired BRB . Additionally, independent groups have reported that a thickening of the perivascular structures can be visualized in exudative vasculitis and monitored with structural OCT scans in patients with birdshot chorioretinopathy . Further studies are needed to establish if these findings can be observed in other uveitic entities.…”
Section: Oct/octa Of the Retina In Uveitismentioning
confidence: 99%
“…Cool colours (green and blue) represent decreased thickness, while warm colours (yellow, orange and red) represent increased thickness. 17 Qualitative analysis of capillary network abnormalities was then compared with FA. Peripheral capillary leakage was compared with flow changes on the wide-field OCTA.…”
Section: Acquisition Of Octa Imagementioning
confidence: 99%